PENGEMBANGAN EDUWISATA GARAM DI DESA BUNDER BAGI PEREKONOMIAN MASYARAKAT - Aprilina Susandini; Roby Gunawan, Ahmad (Universitas Islam Lamongan, 2023)
Salt tourism is one of the unique tours that offers natural scenery in the form of salt fields with piles of salt piled up. This tour is the first salt tour in Madura whis is located in Bunder Village, Pademawu District, Pamekasan Regency. Over time, tourism development is carried out by the manager, namely BUMDes Mutiara Saghara in the hope of increasing the number of visitors. However, the development process requires considerable costs. This must be in line with the benefits that will be obtained. The purpose of this study was to determine the impact of salt eduwisata development on the economy of the surronding community. This research uses a qualitative approach with purposive sampling technique. The results showed that many benefits were felt by the community with the presence of salt eduwisata.